Pendampingan Implementasi Pembelajaran Sosial-Emosional Berbasis Kelas melalui Coaching Reflektif - Herlinawati Herlinawati; Nurfaisal Nurfaisal; M. Firdaus (Journal Of Human And Education (JAHE), 2026)
This community engagement program aimed to strengthen teachers' capacity to integrate social-emotional learning into regular classroom instruction through a workshop, classroom practice, observation, reflective coaching, and evaluation. The partner school was SMA Negeri 2 Tambang, Kampar Regency, Riau, which employed 70 teachers; 43 teachers (61.43%) participated. Evaluation used a teacher-understanding pretest-posttest, observations across 15 units before and 15 units after mentoring, a student response questionnaire, and teacher reflection. The mean understanding score increased from 61.74 to 82.56, a difference of 20.82 score points. The largest difference was found in teachers' ability to integrate social-emotional learning into instruction (22.09 points). After mentoring, supportive teacher-student interaction was observed in 93.3% of observation units, collaboration and empathy in 86.7%, emotion check-ins/reflection in 80.0%, and end-of-lesson reflection in 73.3%. Twelve of 15 observation units displayed at least three SEL strategies. Aggregated positive student responses ranged from 74% to 81%. The findings indicate strengthened teacher understanding and early changes in classroom practice. The data do not establish causality or direct improvement in students' psychological well-being.